Two Case Reports of Benign Testicular Mesothelioma and Review of the Literature - Cristobal Ramirez Sevilla; Carme Admella Salvador; Josep Feliu Canaleta; Juan Llopis Manzanera; Miguel Angel Barranco Sanz; Juan Antoni Romero Martin; Sergi Bernal Salguero (Case Reports in Oncological Medicine)
Mesothelioma is usually diagnosed in people over the age of 50 with large history of asbestos-related exposure. It is frequently located in pleural cavity, peritoneum, and pericardium. At the testicles the mesothelioma had been reported first in 1957 like a malignant non-germ-cells tumor. The objective is to present two case reports of benign testicular mesothelioma and review of the literature.